Co-evolution between the South African venture capital industry and the South [African] government - Aluko, Olumide Mayowa (2011)
This thesis contributes to the current discourse around co-evolution, this study investigates co-evolution between the South African venture capital industry and the South African government. Using a qualitative method which involved gathering data from archival sources and contemporary interviews, this study extends the growing literature on the co-evolution of organizations and their institutional environment in three ways. First, the study shows that the co-evolution that occurs between organizations and the institutional environment, is facilitated by both entities' respective need for legitimate status with different audiences. Second, the study furthers our understanding of co-evolution at the meso level (i.e. the organizational field) by illustrating the place of subject positions of organizations and power in the co-evolution that occurs at that level. Third, from the narrative presented in the study on the emergence of a venture capital industry in South Africa, the study explicates the importance of a free market system in a transition economy as it engenders the growth and development of a venture capital industry in such economies.